Bilateral Semicircular Canal Dehiscence Analyzed Using the International Classification of Functioning, Disability, and Health (ICF) Framework: Case Report - Ignacio Novoa‐Cornejo; Vijaya Prakash Krishnan Muthaiah; Victor Mercado‐Martinez; Gustavo Ulloa‐Alvarado; Carlos Pino‐Urrutia; Krishnamoorthy Gunasekaran (Clinical Case Reports)
ABSTRACT A severe case of bilateral superior semicircular dehiscence was presented in Instituto de Neurorrehabilitación y Balance, Chile. The patient reports hearing and vestibular problems in certain situations; a complete analysis is carried out from the clinical history to neurological laboratory studies and imaging to diagnose bilateral semicircular canal dehiscence finally. Health condition management is under the ICF model, which will allow for determining and classifying the problems and possible interventions for this interesting clinical case.